2022
DOI: 10.3389/fenvs.2022.942441
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of two methods for rare earth elements analysis in human urine samples using inductively coupled plasma-mass spectrometry

Abstract: The application of rare earth elements (REEs) in several areas, including high-tech technology, agriculture, medicine, and fuels, has made them an essential component of our everyday life. This extensive use of REEs in several technologies is expected to potentially impact human health. Even if several studies investigated the levels of REEs in human matrices, until now no standard method has been established for analyzing these elements in human matrices. The sample analysis should be of high quality, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…They concluded that, despite taking longer and being less cost-effective, the MAD method was preferred. A similar comparison was made by Brouziotis et al 45 for the determination of REEs in human urine by ICP-MS: urine was either diluted (1 + 4) with 2% (v/v) HNO 3 or subjected to MAD in a sealed vessel (2 mL urine, 0.5 mL conc. HNO 3 , final volume 10 mL).…”
Section: Sample Collection and Preparationmentioning
confidence: 82%
“…They concluded that, despite taking longer and being less cost-effective, the MAD method was preferred. A similar comparison was made by Brouziotis et al 45 for the determination of REEs in human urine by ICP-MS: urine was either diluted (1 + 4) with 2% (v/v) HNO 3 or subjected to MAD in a sealed vessel (2 mL urine, 0.5 mL conc. HNO 3 , final volume 10 mL).…”
Section: Sample Collection and Preparationmentioning
confidence: 82%
“…For example, Brouziotis et al , 26 developed a methodology for REE analysis in human urine samples and calculated instrumental LODs for ICP-MS in the range of 0.001–0.004 μg L −1 . Kukusamude and Kongsri 47 developed and validated a method for REE determination in rice using ICP-MS and reported LODs between 0.07 and 0.010 μg L −1 .…”
Section: Resultsmentioning
confidence: 99%
“…ICP-MS is known for its susceptibility to isobaric interferences that can affect the accuracy of REE measurements, i.e., the presence of barium oxides can interfere with LREEs such as Nd, Sm and Eu, while oxides of LREEs (e.g., CeO and NdO) interfere with some HREEs (e.g., Gd, Tb, and Dy). 26 Modern ICP-MS instruments are equipped with collision or reaction cells that can eliminate these interferents. For laboratories equipped only with ICP-OES, the development of analytical methods based on this technique and capable of providing accurate results for the analysis of REEs in complex matrices is of great interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation